2015
DOI: 10.1017/s0016756815000801
|View full text |Cite
|
Sign up to set email alerts
|

The riddle of Spinosaurus aegyptiacus’ dorsal sail

Abstract: Spinosaurus aegyptiacus was probably the largest predatory dinosaur of the Cretaceous period. A new study shows that it was a semiaquatic hunter. The function of Spinosaurus' huge dorsal 'sail' remains unsolved, however. Three hypotheses have been proposed: (1) thermoregulation; (2) humpback storage; or (3) display. According to our alternative hypothesis, the submerged sail would have improved manoeuvrability and provided the hydrodynamic fulcrum for powerful neck and tail movements such as those made by sail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Several other dinosaurian taxa have convergently acquired similar structures including those that were sympatric with spinosaurs (Bertin, 2010) and it has also been suggested that bodies of water may have helped large spinosaurs regulate body temperature (Amiot et al, 2010b). It has recently been suggested that the sail in Spinosaurus may have functioned as a mechanical aid during swimming (Gimsa et al, 2015) but this relies on the animal being an able swimmer in deep water and is based on a number of unverifiable assumptions about the anatomy and locomotion of these animals and so is not here considered a viable hypothesis. No detailed work has been done to assess the possible 'mechanical' functions of the sail in these animals, though certainly it would have increased the surface area of the animals considerably and could potentially at least serve as thermoregulatory device (Bertin, 2010), though this does not rule out other hypotheses (Holtz et al, 2004;Bertin, 2010).…”
Section: Ecology and Behaviourmentioning
confidence: 99%
“…Several other dinosaurian taxa have convergently acquired similar structures including those that were sympatric with spinosaurs (Bertin, 2010) and it has also been suggested that bodies of water may have helped large spinosaurs regulate body temperature (Amiot et al, 2010b). It has recently been suggested that the sail in Spinosaurus may have functioned as a mechanical aid during swimming (Gimsa et al, 2015) but this relies on the animal being an able swimmer in deep water and is based on a number of unverifiable assumptions about the anatomy and locomotion of these animals and so is not here considered a viable hypothesis. No detailed work has been done to assess the possible 'mechanical' functions of the sail in these animals, though certainly it would have increased the surface area of the animals considerably and could potentially at least serve as thermoregulatory device (Bertin, 2010), though this does not rule out other hypotheses (Holtz et al, 2004;Bertin, 2010).…”
Section: Ecology and Behaviourmentioning
confidence: 99%
“…These authors cautiously suggested that spinosaurs would have been well adapted to forage in aquatic settings like the eels, but did not say anything about semi-aquatic habits for spinosaurids. A very speculative paper on the swimming abilities of Spinosaurus and the function of the dorsal ‘sail’ by Gimsa, Sleigh & Gimsa (2016) employed qualitative comparisons between crocodilians, large, predatory fishes (both chondrichthyan and osteichthyan) and Spinosaurus . These authors envisaged Spinosaurus as an animal capable of becoming fully immersed and employing lateral undulation in the pursuit of prey.…”
Section: Introductionmentioning
confidence: 99%
“…Spinosaurids are characterised by a highly specialised anatomy, which was originally described on the basis of a partial skeleton of the name-giving genus Spinosaurus from the Cenomanian of Egypt by Stromer (1915). The dorsal and sacral vertebrae have elongated neural spines, likely the support for a large back sail, the function of which (e.g., display, thermoregulation, swimming) has been extensively discussed (Stromer, 1915;Bailey, 1997;Holtz, 1998;Ibrahim et al, 2014;Gimsa et al, 2016;Candeiro et al, 2017). The cranium is long and low with a lateral compression and a long and narrow snout (Dal Sasso et al, 2005;Rayfield et al, 2007).…”
Section: Introductionmentioning
confidence: 99%